Creating the "The Goddess of the Hearth" Panel Using Collage Technique - Svetlana G. Sokolova (Publishing house "Sreda", 2021)
The purpose of the article is to describe one of the forms of professional training of future leaders of the studio of decorative-applied art, namely, the implementation of a creative project of ethnocultural orientation. Students of the Chuvash State Institute of Culture and Arts made a panel in the collage technique «The Goddess of the hearth». At the first stage of the project, the literature on the topic of Chuvash mythology was studied. Based on the analysis of literary sources - the works of P.V. Denisov, V.K. Magnitsky, D. Mesarosh, A.K. Salmin the main characteristics of the deity «Hertsurt» were identified, which is the keeper of the hearth, the goddess of the right ordering of domesticity in Chuvash mythology. The article provides a technical and technological substantiation of the manufacturing process and describes in detail the sequence of creating the panel «The Goddess of the hearth». The author emphasizes that authentic patterns for embroidery were used, as well as traditional for the Chuvash colors, elements of clothing, utensils. It is noted that the project as a whole contributed to the formation of the main professional competencies of future leaders of the studio of decorative-applied art - to have the skills of making art products in folk traditions.